Preparation method of hydroxyapatite pre-filling needle capable of quickly taking effect, efficiently and slowly releasing

By using low-viscosity and medium-viscosity sodium carboxymethylcellulose combined with calcium salt solution, the lattice expansion and release rate of hydroxyapatite is controlled, and the hydroxyapatite particles are easily agglomerated during preparation, storage and use. The problem of agglomeration achieves the unity of rapid onset, efficient and slow release, and improves the stability of pre-filling needles.

CN119185649APending Publication Date: 2024-12-27DONGFANG YANMEI (CHENGDU) BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202411333671.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Hydroxyapatite particles tend to agglomerate during preparation, storage and use, resulting in performance losses, making it difficult to achieve the unity of rapid onset and slow release. At the same time, solid-liquid separation and redispersion are required, which increases process cost and stability. question.

Method used

Using a combination of low-viscosity and medium-viscosity sodium carboxymethylcellulose and calcium salt solution, a colloidal solution is formed by adjusting the pH value and temperature, and phosphate or biphosphate is added to control the lattice expansion and release of hydroxyapatite. Speed, avoid aggregation and precipitation, and improve stability.

Benefits of technology

The rapid onset, efficient and slow release of hydroxyapatite pre-filled needles is achieved, which avoids the trouble of solid-liquid separation and re-aggregation, and improves the stability and dispersion of pre-filled needles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057692410000071
    Figure BDA0005057692410000071
  • Figure BDA0005057692410000091
    Figure BDA0005057692410000091
  • Figure BDA0005057692410000101
    Figure BDA0005057692410000101
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydroxyapatite pre-filling needle, which comprises the following steps: dispersing low-viscosity sodium carboxymethyl cellulose in water, adding a calcium salt solution, and uniformly mixing, so that part of sodium ions are replaced by calcium ions; adding a sodium carboxymethyl cellulose solution with medium viscosity; 3) adding a solution of phosphate or hydrophosphate or dihydric phosphate or a mixed salt of phosphate or hydrophosphate or dihydric phosphate, adjusting the pH value to 10-11, uniformly mixing, and standing for 1-7 days C, wherein the amount of phosphate ions is 40-60% of the amount of calcium ions; a calcium salt solution is added, the amount of calcium ions accounts for 60%-80% of the total amount of positive ions in the low-viscosity carboxymethyl cellulose and the medium-viscosity carboxymethyl cellulose, and the mixture is evenly mixed and aged for 1-7 days; and if necessary, filtering by using a nanofiltration membrane to remove small molecular substances. The pre-filling needle can achieve the unification of quick effect, high efficiency and slow release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A method for preparing a hydroxyapatite prefilled needle. Specifically, the invention relates to a method for preparing a hydroxyapatite prefilled needle with rapid onset, high efficiency and slow release. Technical Background

[0002] Medical grade hydroxyapatite (HAP) microspheres have been widely used in the medical and biological fields due to their special structure and chemical composition. They are mainly used in bone repair, implant support, drug sustained release, etc.

[0003] For example, a prefilled needle composed of hydroxyapatite microspheres, sodium hyaluronate, sodium carboxymethylcellulose, and lidocaine hydrochloride can be used for subcutaneous implantation to correct moderate to severe nasolabial wrinkles.

[0004] Compared with bulk or micron HAP, nano-HAP has a larger specific surface area and exhibits higher performance. However, nano-HAP is prone to agglomeration during preparation, use and storage, resulting in performance loss and limiting its use effect, for example, it is difficult to achieve the unity of slow release, rapid onset and high efficiency.

[0005] The HAP particles currently prepared need to be separated from the solid and liquid and re-dispersed in the liquid for use, which increases the process cost.

[0006] Therefore, in reality, it is necessary to overcome the trouble of solid-liquid separation of HAP particles during the preparation process, the trouble of re-aggregation during the preparation, storage and use, the trouble of re-dispersion in liquid, and the problem of poor stability of re-aggregation after dispersion.

[0007] Therefore, there is a real need for a prefilled needle containing hydroxyapatite microspheres, which can achieve the unity of rapid onset, high efficiency and slow release, while avoiding the above problems. Summary of the invention

[0008] Based on the above needs, the purpose of the present invention is to provide a method for preparing a hydroxyapatite prefilled needle, which overcomes the troubles of HAP (hydroxyapatite) particles needing to be separated from the solid and liquid during the manufacturing process and re-aggregating during the storage process after separation, as well as the trouble of needing to re-disperse HAP in a liquid and the trouble of re-aggregating after dispersion. The preparation method can also achieve the unity of rapid onset, high efficiency and slow release, and the preparation method also improves the stability of the prefilled needle.

[0009] The present invention relates to a method for preparing a fast-acting, highly effective and sustained-release hydroxyapatite prefilled needle, the method comprising:

[0010] 1) Dispersing sodium carboxymethyl cellulose with a substitution degree of 0.7-1, a sodium content of 7-9% wt / wt (neutralization degree of 90-100%) and low viscosity in water, adding a calcium salt solution, and mixing well so that 40% to 70% (in moles) of the sodium ions are replaced by calcium ions to form a colloidal solution A, wherein the content or concentration of sodium carboxymethyl cellulose in the solution is 5-20% wt / v, and the viscosity of the sodium carboxymethyl cellulose at a concentration of 1% wt / v is 5-30 mPa·s;

[0011] 2) Adding 0.5-2 times the weight or volume of a medium-viscosity sodium carboxymethyl cellulose solution to colloidal solution A to obtain colloidal solution B, wherein the content or concentration of the medium-viscosity sodium carboxymethyl cellulose in the solution is 1-10% wt / v, the viscosity of the sodium carboxymethyl cellulose at a concentration of 1% wt / v is 800-2500 mPa·s, and the sodium content of the sodium carboxymethyl cellulose is 7-9% wt / wt (neutralization degree is 90-100%);

[0012] 3) Add a solution of phosphate or hydrogen phosphate or dihydrogen phosphate or a mixed salt thereof to the colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) is 40% to 60% of the amount (molar number) of the above calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment at a temperature of 25-35° C. for 1-7 days to obtain a colloidal solution C;

[0013] 4) Adding calcium salt solution to colloidal solution C, wherein the amount (molar number) of calcium ions is 60% to 80% of the total amount (molar number) of positive ions in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, mixing, aging at room temperature 25-35° C. for 1-7 days, to obtain colloidal solution D;

[0014] 5) If necessary, the colloidal solution D is filtered through a nanofiltration membrane with a pore size of 200 Da to remove small molecules. DETAILED DESCRIPTION

[0015] The sodium content of the low-viscosity or medium-viscosity sodium carboxymethyl cellulose is preferably 7-8% wt / wt, more preferably 7.5-8% wt / wt.

[0016] The content or concentration of the low-viscosity sodium carboxymethyl cellulose is 10-20% wt / v.

[0017] The viscosity of the low-viscosity sodium carboxymethyl cellulose is 10-15 mPa·s at a concentration of 1% wt / v.

[0018] The content or concentration of the above-mentioned medium-viscosity sodium carboxymethyl cellulose is 2-6% wt / v.

[0019] The above calcium salts include but are not limited to calcium chloride, calcium acetate, calcium nitrate, calcium hydroxide or mixtures thereof.

[0020] The above-mentioned phosphates, hydrogen phosphates or dihydrogen phosphates include but are not limited to potassium salts, sodium salts and ammonium salts thereof.

[0021] The amount (molar number) of phosphate ions (or phosphorus) in the solution of the above-mentioned phosphate, hydrogen phosphate, dihydrogen phosphate or a mixed salt thereof is 50% to 55% of the amount (molar number) of calcium ions.

[0022] The colloidal solution D is preferably aged for 3-5 days.

[0023] The prefilled needle of the present invention may also contain sodium hyaluronate, sodium carboxymethyl cellulose with a relatively high viscosity, glycerin, lidocaine, and water.

[0024] The advantage of using low-viscosity sodium carboxymethyl cellulose in the present invention is that it maintains a relatively low viscosity at a higher concentration, which is conducive to the replacement of calcium ions by sodium ions in the central part, and is conducive to increasing the calcium content. When using high-viscosity sodium carboxymethyl cellulose, it is easy to cause the sodium ions in the surface layer to be replaced by calcium ions to form a relatively viscous boundary layer, which hinders the replacement of sodium ions and calcium ions in the inner layer, and is not conducive to increasing the calcium content and uniform dispersion.

[0025] The present invention allows a part of sodium ions in sodium carboxymethyl cellulose to be retained instead of being completely replaced by calcium ions, which is beneficial to maintaining relatively high hydrophilicity, and the viscosity is not particularly large, and it is not easy to cause aggregation or precipitation.

[0026] When the present invention adds a solution of phosphate or hydrogen phosphate or dihydrogen phosphate or a mixed salt thereof to form hydroxyapatite, a small portion of calcium in the carboxyl cellulose is preferably retained, so that the carboxyl cellulose can maintain a certain (or relatively high) viscosity, which is beneficial to prevent the hydroxyapatite lattice from expanding and prevent the formation of larger hydroxyapatite particles.

[0027] The present invention adopts sodium carboxymethyl cellulose with medium viscosity, which is conducive to delaying the expansion of hydroxyapatite lattice and preventing the formation of larger hydroxyapatite particles; at the same time, the carboxymethyl cellulose maintains a relatively high viscosity, which is conducive to the slow release of hydroxyapatite. High molecular weight sodium carboxymethyl cellulose is not conducive to the formation of hydroxyapatite. Specifically, due to the high viscosity, the combination of phosphate ions and calcium ions slows down, resulting in a long reaction time or incomplete reaction. In addition, high viscosity sodium carboxymethyl cellulose is not conducive to the preparation and clinical use of pre-filled needles.

[0028] The present invention adds a calcium salt solution to calcify medium-low viscosity sodium carboxymethyl cellulose when aging hydroxyapatite, and does not use high-viscosity sodium carboxymethyl cellulose, so that the hydroxyapatite release can be moderate and not too small, and is conducive to further preventing the expansion of the hydroxyapatite lattice and preventing the formation of larger hydroxyapatite particles, thereby facilitating the rapid release of the base apatite to achieve the purpose of high efficiency. After calcification, the viscosity of high-viscosity sodium carboxymethyl cellulose becomes too large, so that the release of hydroxyapatite is too slow. In addition, high-viscosity sodium carboxymethyl cellulose is easy to precipitate or aggregate after calcification, which is not conducive to the preparation and clinical use of pre-filled needles.

[0029] When the hydroxyapatite is aged in the present invention, a calcium salt solution is added to make the medium-low viscosity carboxymethyl cellulose sodium salt or other salt (phosphate or hydrogen phosphate or dihydrogen phosphate, with positive ions such as sodium ions, NH4+) calcify most of the positive ions, rather than a small amount or all of them, so that the sustained release rate is moderate, not too large or too small or uncertain. The calcification of a small part of the positive ions makes the solution viscosity low, and the hydroxyapatite is released too quickly, which is not conducive to sustained release. The complete calcification of the positive ions easily causes the carboxyl cellulose to aggregate or precipitate, and the release rate of hydroxyapatite is uncertain, which is also not conducive to sustained release.

[0030] The advantages of the present invention over the prior art are:

[0031] 1) It overcomes the trouble of HAP particles needing solid-liquid separation during the preparation process and reaggregation during the preparation, storage and use process;

[0032] 2) It overcomes the trouble of HAP particles needing to be redispersed in the liquid;

[0033] 3) and overcome or delay the trouble of HAP particles reaggregating after dispersion;

[0034] 4) Improved the stability of the prefilled needle.

[0035] 5) It can achieve the unity of rapid effect, high efficiency and slow release.

[0036] Example

[0037] The following non-optional example, i.e., the method for preparing a prefilled needle, further describes a preferred embodiment within the scope of the present invention. There are many variations of these embodiments within the scope of the present invention.

[0038] Example 1

[0039] 1) Disperse sodium carboxymethyl cellulose (Akucell AF 0305) with a substitution degree of 0.7-0.95 and a sodium content of about 8% wt / wt (neutralization degree of 95-100%) and low viscosity (viscosity of 10-15 mPa·s at a concentration of 1% wt / v) in 100 g of water, wherein the content of sodium carboxymethyl cellulose in the solution is 7% wt / v, add 10% calcium chloride salt solution, mix well, and make about 65% (molar number) of sodium ions replaced by calcium ions to form colloidal solution A;

[0040] 2) Add 0.8 times the weight of medium viscosity sodium carboxymethyl cellulose solution (AkucellAF 2785W) to colloidal solution A, mix well, and obtain colloidal solution B, wherein the content or concentration of medium viscosity sodium carboxymethyl cellulose in the solution is 3% wt / v, the viscosity of the sodium carboxymethyl cellulose at a concentration of 1% wt / v is 1500-2500 mPa·s, and the sodium content of the sodium carboxymethyl cellulose is about 7.9% wt / wt (neutralization degree is 90-100%);

[0041] 3) Add 6% sodium hydrogen phosphate solution to colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) is 45% of the amount (molar number) of the above calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment at a temperature of 25-35° C. for 72 hours to obtain colloidal solution C;

[0042] 4) Add 3.5% wt / v calcium chloride salt solution to colloidal solution C, wherein the amount (molar number) of calcium ions is 75% of the total amount (molar number) of sodium ions (or positive ions) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, mix well, and age at room temperature 25-35° C. for 7 days to obtain colloidal solution D;

[0043] 5) The colloidal solution D is filtered through a nanofiltration membrane with a pore size of 200 Da to remove small molecules.

[0044] Comparative Example 1-1

[0045] The sodium carboxymethylcellulose (Akucell AF 0305) in Example 1 was replaced with Akucell AF 1985 (whose viscosity was 110-200 mPa·s at a concentration of 1% wt / v), and the rest remained unchanged.

[0046] Comparative Example 1-2

[0047] The content or concentration of the medium viscosity sodium carboxymethyl cellulose of 3% wt / v in Example 1 was replaced with the content or concentration of the medium viscosity sodium carboxymethyl cellulose of 0.3% wt / v, and the others remained unchanged.

[0048] As in Example 1-3

[0049] The content or concentration of the medium viscosity sodium carboxymethyl cellulose in Example 1 is 3% wt / v, while the content or concentration of the medium viscosity sodium carboxymethyl cellulose is 10% wt / v, and the others remain unchanged.

[0050] Comparative Examples 1-4

[0051] The amount (molar number) of calcium ions in Example 1 is 75% of the amount (molar number) of the total amount (molar number) of sodium ions (or positive ions) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and is replaced with an amount (molar number) of calcium ions being 100% of the amount (molar number) of the total amount (molar number) of sodium ions (or positive ions) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, while the others remain unchanged.

[0052] Comparative Examples 1-5

[0053] The amount (molar number) of calcium ions in Example 1 is 75% of the amount (molar number) of the total amount (molar number) of sodium ions (or positive ions) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and is replaced with the amount (molar number) of calcium ions in Example 1 is 20% of the amount (molar number) of the total amount (molar number) of sodium ions (or positive ions) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and the others remain unchanged.

[0054] Comparative Examples 1-6

[0055] Take the same amount of low-viscosity sodium carboxymethyl cellulose (Akucell AF 0305) and medium-viscosity sodium carboxymethyl cellulose solution (Akucell AF 2785W) as in Example 1, disperse them in an appropriate amount of water, add commercially available hydroxyapatite (microsphere state, factory-labeled particle size: 25-80 nm), wherein the amount (molar number) of phosphate ions (or phosphorus) is the same as the amount (molar number) of phosphate ions (or phosphorus) in the added diammonium phosphate salt, and add an appropriate amount of water to make the volume the same as the final volume of Example 1.

[0056] Example 2

[0057] 1) Disperse sodium carboxymethyl cellulose (Akucell AF 0305) with a substitution degree of 0.7-0.95 and a sodium content of about 8% wt / wt (neutralization degree of 95-100%) and low viscosity (viscosity of 10-15 mPa·s at a concentration of 1% wt / v) in 100 g of water, wherein the content of sodium carboxymethyl cellulose in the solution is 16% wt / v, add 15% calcium nitrate salt solution, mix well, and make about 45% (molar number) of sodium ions replaced by calcium ions to form colloidal solution A;

[0058] 2) Add 1.5 times the weight of medium viscosity sodium carboxymethyl cellulose solution (Akucell AF2405) to colloidal solution A, mix well, and obtain colloidal solution B, wherein the content or concentration of medium viscosity sodium carboxymethyl cellulose in the solution is 8% wt / v, the viscosity of the sodium carboxymethyl cellulose at a concentration of 1% wt / v is 800-1200 mPa·s, and the sodium content of the sodium carboxymethyl cellulose is about 8% wt / wt (neutralization degree is 90-100%);

[0059] 3) Add 5% diammonium phosphate solution to colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) is 55% of the amount (molar number) of the above calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment with a temperature of 25-35° C. for 5 days to obtain colloidal solution C;

[0060] 4) Add 3.5% wt / v calcium nitrate salt solution to colloidal solution C, wherein the amount (molar number) of calcium ions is 65% of the total amount (molar number) of positive ions in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, mix well, and age at room temperature 25-35° C. for 5 days to obtain colloidal solution D;

[0061] 5) The colloidal solution D is filtered through a nanofiltration membrane with a pore size of 200 Da to remove small molecules.

[0062] Comparative Example 2-1

[0063] In Example 2, about 45% (in moles) of sodium ions are replaced by calcium ions to form colloidal solution A.

[0064] Replace with

[0065] About 100% (in moles) of sodium ions are replaced by calcium ions to form colloidal solution A.

[0066] and

[0067] A 5% solution of ammonium dihydrogen phosphate salt was added to the colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) was the same as the amount (molar number) of phosphate ions (or phosphorus) in Example 2, and the others remained unchanged.

[0068] Comparative Example 2-2

[0069] The content or concentration of the medium viscosity sodium carboxymethyl cellulose of 8% wt / v in Example 2 was replaced with the content or concentration of the medium viscosity sodium carboxymethyl cellulose of 0.4% wt / v, and the others remained unchanged.

[0070] As in Example 2-3

[0071] The content or concentration of the medium viscosity sodium carboxymethyl cellulose of 8% wt / v in Example 2 was replaced with the content or concentration of the medium viscosity sodium carboxymethyl cellulose of 16% wt / v, and the others remained unchanged.

[0072] Comparative Example 2-4

[0073] The amount (molar number) of calcium ions in Example 2 is 65% of the total amount (molar number) of positive ions in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and is replaced with the amount (molar number) of calcium ions in Example 2 is 100% of the total amount (molar number) of positive ions in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and the rest remains unchanged.

[0074] Comparative Example 2-5

[0075] The amount of calcium ions (molar number) in Example 2 is 65% of the total amount of positive ions (molar number) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and is replaced with the amount of calcium ions (molar number) in Example 2 is 10% of the total amount of positive ions (molar number) in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, and the rest remains unchanged.

[0076] Comparative Example 2-6

[0077] Take the same amount of low-viscosity sodium carboxymethyl cellulose (Akucell AF0305) and medium-viscosity sodium carboxymethyl cellulose solution (Akucell AF2405) as in Example 2, disperse them with an appropriate amount of water, add commercially available hydroxyapatite (microsphere state, factory-labeled particle size: 25-80nm), wherein the amount (molar number) of phosphate ions (or phosphorus) is the same as the amount (molar number) of phosphate ions (or phosphorus) in the added diammonium phosphate salt, and add an appropriate amount of water to make the volume the same as the final volume of Example 1.

[0078] Test Example 1

[0079] The samples of the embodiment and the control example were diluted with purified water at a ratio of 1:10 and placed at room temperature. After 0 month, 1 month, 2 months, 4 months and 6 months, samples were taken and the turbidity values ​​(NTU) were measured using a Hach turbidometer.

[0080] The results are shown in Table 1.

[0081] Table 1-1 Turbidity values ​​(NTU) measured in Example 1 and its comparative example

[0082] 0 month January February April June Example 1 3.2 3.4 3.7 4.2 4.7 Comparative Example 1-1 5.6 8.8 13.5 20.2 28.6 Comparative Example 1-2 4.6 5.5 8.2 13.7 20.2 Comparative Examples 1-4 23.7 40.8 65.9 103.7 145.9 Comparative Examples 1-5 14.6 22.8 35.8 60.4 92.3 Comparative Examples 1-6 27.5 47.9 74.2 122.7 172.5

[0083] Table 1-2 Turbidity values ​​(NTU) measured in Example 2 and its comparative example

[0084]

[0085]

[0086] The results show that the embodiment has lower turbidity value, better dispersion, smaller particles, and significantly better storage stability than the control example.

[0087] Test Example 2

[0088] The samples of the embodiment and the control example were prepared into pre-filled needles according to the ratio of sample: sodium hyaluronate: glycerol: lidocaine hydrochloride: water = 30:2:10:0.3:57.7, and sterilized by γ-ray irradiation.

[0089] Animal in vivo toxicity tests, cytotoxicity tests, pyrogen tests, hemolysis tests and intradermal injection experiments have demonstrated that the prefilled needle is non-toxic, has no hemolytic effect, is non-irritating, does not contain pyrogenic substances, has stable performance and good biocompatibility.

[0090] 256 patients with moderate to severe nasolabial wrinkles were subcutaneously injected with 2 mL of the above prefilled needle on both sides of the face, and the efficacy of the prefilled needle containing the embodiment and the control example was compared and observed in 1 month, 2 months and 4 months.

[0091] Observation indicators

[0092] Effectiveness evaluation

[0093] (1) Effectiveness of wrinkle correction: The researchers used the 5-level grading method of WSRS to grade wrinkles: Grade 1 (absent), no obvious nasolabial folds, continuous skin line; Grade 2 (mild), shallow but visible nasolabial folds with slight creases, mild facial features; Grade 3 (moderate), deep nasolabial folds, clear facial features visible in normal appearance, but not visible when stretched; Grade 4 (severe), very long and deep nasolabial folds, prominent facial features, visible wrinkles <2 mm when stretched; Grade 5 (extremely severe), extremely deep and long nasolabial folds, detrimental to facial appearance, V-shaped wrinkles visible when stretched 2-4 mm.

[0094] The standard for judging the effectiveness of wrinkle correction is that the WSRS grade is reduced by at least one after treatment compared with before treatment. Wrinkle correction effectiveness = number of subjects with effective wrinkle correction / number of subjects × 100%. The researchers evaluated the wrinkle correction effectiveness of the subjects 1 month, 2 months and 4 months after treatment according to the WSRS rating scale. If the WSRS grades of the bilateral nasolabial folds of the same subject are inconsistent, the grade of the side with the worse effect (i.e., the side with the higher WSRS grade) is taken.

[0095] (2) WSRS score: The researchers evaluated the WSRS scores of the subjects before treatment and 1 month, 2 months, and 4 months after treatment according to the WSRS rating scale.

[0096] Data processing

[0097] SPSS 23.0 software was used for statistical analysis. Count data were expressed as percentages, and the comparison of observation indicators at different times after treatment was performed using the χ2 test. Measurement data were expressed as mean ± standard deviation, and the comparison before and after treatment and at different times after treatment was performed using the t test. P < 0.05 indicated statistically significant differences.

[0098] The results of the effective rate of nasolabial fold wrinkle correction of the subjects who received the sample treatment at 1 month, 2 months and 4 months after the treatment are shown in Table 2.

[0099] Table 3 shows the WSRS score results of the subjects before and 1 month, 2 months and 4 months after the sample treatment.

[0100] Table 2-1 Effectiveness of nasolabial wrinkle correction in Example 1 and its control example 1 month, 2 months and 4 months after treatment (%)

[0101] January February April Example 1 56.7 77.2 95.2 Comparative Examples 1-3 26.3 40.3 75.3 Comparative Examples 1-4 20.3 33.4 58.2 Comparative Examples 1-5 30.6 52.8 82.8 Comparative Examples 1-6 15.3 26.6 50.6

[0102] Table 2-2 Effectiveness of nasolabial wrinkle correction in Example 2 and its control example 1 month, 2 months and 4 months after treatment (%)

[0103]

[0104]

[0105] Table 3-1 WSRS scores of Example 1 and its control example 1 month, 2 months and 4 months after treatment

[0106] 0 month January February April Example 1 3.36±0.37 2.72±0.64 2.38±0.62 2.15±0.45 Comparative Examples 1-3 3.31±0.42 3.12±0.61 2.93±0.53 2.71±0.48 Comparative Examples 1-4 3.32±0.38 3.21±0.65 3.05±0.48 2.84±0.49 Comparative Examples 1-5 3.37±0.35 2.95±0.68 2.78±0.57 2.58±0.54 Comparative Examples 1-6 3.38±0.39 3.27±0.68 3.11±0.53 2.97±0.53

[0107] Table 3-2 WSRS scores of Example 2 and its control example 1 month, 2 months and 4 months after treatment

[0108] 0 month January February April Example 2 3.47±0.43 2.70±0.65 2.31±0.53 2.03±0.42 Comparative Example 2-3 3.49±0.52 3.03±0.65 2.91±0.68 2.76±0.62 Comparative Example 2-4 3.43±0.47 3.14±0.63 3.03±0.61 2.83±0.62 Comparative Example 2-5 3.46±0.54 2.95±0.62 2.80±0.63 2.67±0.58 Comparative Example 2-6 3.43±0.47 3.32±0.68 3.14±0.65 2.93±0.66

[0109] The results show that the embodiment has faster efficacy and higher efficacy than the control example.

[0110] Test Example 3

[0111] In vitro effective ion dissolution test

[0112] The samples of the embodiment and the reference example were prepared into pre-filled needles according to the ratio of sample: sodium hyaluronate: glycerol: lidocaine hydrochloride: water = 30:2:10:0.3:57.7. 20 ml of the pre-filled needle samples of the embodiment and the reference example were taken and placed in a dialysis bag with a pore size of 200 Da, and placed in a sealed constant temperature water tank with a temperature of 37°C and 5000 ml of water without deionized water with a stirrer (stirring for 5 minutes every 1 hour). Five samples were taken after 1 month, 2 months, 3 months and 4 months respectively. ml, and at the same time add 5 ml of deionized water, determine the molar concentration of calcium ions or phosphorus (acid) ions dissolved in the 5 ml sample, and determine the amount (moles) of hydroxyapatite in the above 20 ml pre-filled syringe sample of the embodiment and the reference example, and calculate the percentage of the molar amount of dissolved calcium ions or phosphorus (acid) ions to the molar amount of hydroxyapatite calcium ions or phosphorus (acid) ions in the embodiment or the reference example sample (the above 20 ml), that is, the dissolution percentage (%).

[0113] The results are shown in Table 4.

[0114] Table 4-1

[0115] The results of determination of the percentage (%) of calcium ions and phosphorus (acid) ions dissolved in the samples of Example 1 and its control example

[0116]

[0117] Table 4-2 Results of determination of the percentage (%) of calcium ions and phosphorus (acid) ions dissolved in samples of Example 2 and its comparative example

[0118]

[0119] The results showed that the example samples had faster and better dissolution characteristics than the conventional samples, and had sustained-release characteristics.

Claims

1. A method for preparing a fast-acting, high-efficiency, sustained-release hydroxyapatite prefilled needle, the method comprising: 1) Dispersing sodium carboxymethyl cellulose with a substitution degree of 0.7-1, a sodium content of 7-9% wt / wt, a neutralization degree of 90-100% and low viscosity in water, adding a calcium salt solution, and mixing well so that 40% to 70% of the molar amount of sodium ions therein are replaced by calcium ions to form a colloidal solution A, wherein the content or concentration of sodium carboxymethyl cellulose in the solution is 5-20% wt / v, and the viscosity of the sodium carboxymethyl cellulose at a concentration of 1% wt / v is 5-30 mPa·s; 2) Adding 0.5-2 times the weight or volume of a medium-viscosity sodium carboxymethyl cellulose solution to colloidal solution A to obtain colloidal solution B, wherein the content or concentration of the medium-viscosity sodium carboxymethyl cellulose in the solution is 1-10% wt / v, the viscosity of the sodium carboxymethyl cellulose at a concentration of 1% wt / v is 800-2500 mPa·s, the sodium content of the sodium carboxymethyl cellulose is 7-9% wt / wt, and the degree of neutralization is 90-100%; 3) Add a solution of phosphate or hydrogen phosphate or dihydrogen phosphate or a mixed salt thereof to the colloidal solution B, wherein the molar amount of phosphate ions or phosphorus is 40% to 60% of the molar amount of the calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment at a temperature of 25-35° C. for 1-7 days to obtain a colloidal solution C; 4) Add calcium salt solution to colloidal solution C, wherein the molar amount of calcium ions is 60% to 80% of the molar amount of total positive ions in the above-mentioned low-viscosity carboxymethyl cellulose and medium-viscosity carboxymethyl cellulose, mix well, and age at room temperature 25-35° C. for 1-7 days to obtain colloidal solution D.

2. The preparation method according to claim 1, characterized in that The sodium content of the low-viscosity or medium-viscosity sodium carboxymethyl cellulose is 7-8% wt / wt.

3. The preparation method according to claim 1, characterized in that The content or concentration of the low-viscosity sodium carboxymethyl cellulose is 10-20% wt / v.

4. The preparation method according to claim 1, characterized in that The low-viscosity sodium carboxymethyl cellulose has a viscosity of 10-15 mPa·s at a concentration of 1% wt / v.

5. The preparation method according to claim 1, characterized in that The content or concentration of the medium-viscosity sodium carboxymethyl cellulose is 2-6% wt / v.

6. The preparation method according to claim 1, characterized in that The calcium salt includes calcium chloride, calcium acetate, calcium nitrate, calcium hydroxide or a mixture thereof.

7. The preparation method according to claim 1, characterized in that The phosphate, hydrogen phosphate or dihydrogen phosphate includes potassium salt, sodium salt and ammonium salt thereof.

8. The preparation method according to claim 1, characterized in that The amount (in moles) of phosphate ions (or phosphorus) in the solution of phosphate, hydrogen phosphate, dihydrogen phosphate or a mixed salt thereof is 50% to 55% of the amount (in moles) of calcium ions.

9. The preparation method according to claim 1, characterized in that The colloidal solution B is aged for 3-5 days.

10. The preparation method according to claim 1, characterized in that The prefilled needle may further contain one or more of sodium hyaluronate, sodium carboxymethyl cellulose with higher viscosity, glycerol, lidocaine, and water.

Citation Information

Patent Citations

  • Implantation compositions for use in tissue augmentation

    CN101610796A

  • Hydroxyapatite-containing injection filling preparation and preparation method thereof

    CN110292655A

  • Calcium hydroxyapatite particles and use thereof

    US20240074954A1

Cited By

  • Preparation method and application of cross-linked carboxymethyl cellulose

    CN120647782A